The Peculiarities of Production Programs Planning in the Enterprises Network - Khadzhynova, Olena; Kravchenko, Maryna; Bilous-Sergieieva, Svitlana; Sivitska, Svitlana (International Journal of Engineering and Technology, 2018)
The operation of business networks is characterized by the complexity of the interaction of enterprises within the network. The main means of reconciling the interests of the owners of enterprises, goals and strategies of the participants are business network planning procedures. Through coordinated planning of production activities it should be possible to justify the integration options; to determine the structure of sales and purchases, the expected results of operations, as well as offers to network partners.The article describes the models of production planning of business networks and methodology of constructing a system of coordinated planning. Using the model of coordinated production planning allows to solve the following problems consistently and iteratively: basic coordinated production planning in conditions where demand is known; optimal planning that takes into account random external demand, which results are deterministic input parameters for the first task; optimization of the system test viability of business networks by controlling domestic product prices, the results of which are inputs for the second task.Â Â